2001
DOI: 10.1590/s0100-29452001000200020
|View full text |Cite
|
Sign up to set email alerts
|

Uso Do Índice De Degradação De Amido Na Determinação Da Maturidade Da Manga 'Tommy Atkins'

Abstract: Instalou-se um experimento com manga 'Tommy Atkins' objetivando estudar a eficiência do índice de degradação de amido visando a sua utilização em nível de campo como mais uma alternativa para estimar a maturação dos frutos. A eficácia do método foi estabelecida pela sua correlação durante a maturação com o conteúdo de amido e com a coloração da casca, coloração da polpa, firmeza da polpa, pH, acidez total titulável, sólidos solúveis totais e açúcares redutores e não redutores. O ensaio foi instalado em delinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0
14

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 5 publications
4
6
0
14
Order By: Relevance
“…Similar results were found by Rocha et al (2001), who observed pH rise along maturation, varying from 3.23 to 4.51 for stages 1 and 5, respectively. SS content increased with mango maturity, regardless of injuring.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Similar results were found by Rocha et al (2001), who observed pH rise along maturation, varying from 3.23 to 4.51 for stages 1 and 5, respectively. SS content increased with mango maturity, regardless of injuring.…”
Section: Resultssupporting
confidence: 89%
“…The contents of reducing sugars found here are above those reported by Silva et al (2012), who referred to 2.94% in ‗Tommy Atkins' mangoes. However, our findings match those by Rocha et al (2001) and by Morais et al (2002). In general, maturation promotes sugar increment, mainly owning to hydrolysis of reserve carbohydrates stored during fruit growth on the plant, producing total soluble sugars (TSS) (WILLS et al, 1998).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Além disso, pelo valor de pH e SS observados (Pfaffenbach et al, 2003), pressupõe-se que as mesmas foram colhidas em um estádio de maturação mais avançado, o que, segundo os próprios autores, pode ter reduzido a vida de prateleira das mangas, mesmo sob condições de atmosfera refrigerada. Rocha et al (2001) encontraram valores de pH variando entre 3,23 a 4,51 para mangas Tommy Atkins nos estádios 'verde' a 'traços de verde'. O mesmo foi observado neste experimento, onde, ao final de 35 dias, os frutos da variedade Tommy Atkins apresentaram valores médios de pH de 3,46, e a variedade Haden, de 3,48 (Tabela 1).…”
Section: Resultsunclassified